Conceptual Metaphor in Lonestar Song Lyrics “I’m Already There”: A Cognitive Stylistic Analysis - Atikah Auni Nasution; Desna Uli Matanari; Afiqah Fianda; Rheina Sasmita; Rahmadsyah Rangkuti (Humanitatis : Journal of Language and Literature, 2024)
Metaphor is one of the most effective strategies for making literary works more evocative, striking, and beautiful. Metaphor's significance goes beyond literature to cognitive stylistics, which studies the cognitive processes that underpin language use and interpretation. This study aims to explain the types of conceptual metaphors found in the Lonestar song lyrics "I'm Already There" using Lakoff and Johnson's conceptual theory. The research method used in this study is a descriptive-qualitative method. The research results show that there are 7 conceptual metaphors found in Lonestar's song lyrics "I'm Already There". The results revealed that it contains all forms of conceptual metaphors. Structural metaphors were the most common (43%). Followed by ontological metaphors were also popular (43%). While orientational was the least (14%). Thus, both structural and orientational metaphors dominated the lyrics of "I'm Already There" by Lonestar. This use of metaphorical language incorporates both abstract and physical components, setting the song's narrative apart from others. Overall, the use of structural and ontological metaphors in Lonestar's "I'm Already There" highlights their significant impact on the song's lyrical composition.